INTERFERENCE OF MENTAWAI LANGUAGE PHONOLOGY INTO THE INDONESIAN STUDENTS CLASS X.I SMA NEGERI I SOUTHERN DISTRICT REGENCY OF MENTAWAI ISLANDS - M.Pd, Eva Fitrianti (RC-INSTITUT, 2018)
Phonological interference occurs because of students' negative attitudes toward the use of the Indonesian language. This attitude can be seen in the form of ignorance of the phonological rules of Indonesian language used in the taking of elements of the phonologist that he mastered. The purpose of this study is to describe the form of interference phonology in Mentawai language into the Indonesian class X.I students SMA Negeri I District of Pagai Selatan Mentawai Islands. This research uses qualitative method with descriptive description. The data were collected by using data reduction techniques, presenting the data, and summarizing the data that have been analyzed. The result of this research is that there are three forms of Mentawai phonological interference into the Indonesian language speech of the students of grade XI SMA Negeri 1 Pagai Selatan Kabupaten Mentawai Islands, namely (a) phonological interference reduction of letters at the beginning of word, middle, and end of word, (b) interference of adding letters at the beginning of word, middle and end of word , and (c) interference of letter changes at the beginning of word, middle, and end of word. Factors causing the phonological interference of Mentawai language into Indonesian language class X.I students of SMA Negeri 1 Pagai Selatan Regency of Mentawai Islands are the factors of individual ability, speaker's nobility, the thinness of the speaker's loyalty in using Indonesian language, and the limited mastery of Indonesian vocabulary. Keywords: Interference, phonology, Mentawai language, students.